Feasibility of mechanized bolting rigs in tunneling projects - Harpila, Anna (2013)
Although mechanized bolting rigs have been marketed and used in mining operations for decades, they have seldom been used in tunnelling projects in Finland. Thus, the aim of this thesis is to define the feasibility of mechanized bolting rigs for this purpose and location. This thesis includes an overview about bolting rigs produced by Atlas Copco and Sandvik. The overview is based on information given by manufacturers. In addition, field experience about operating whit Atlas Copco's mechanizes bolting rigs is collected from operations run by Lemminkäinen Corporation. The safety effects of using bolting rigs are analysed based on general hazards of bolting work and on reported accidents in Lemminkäinen Infra Oy, a metro-line extension project in Finland (Länsimetro), and the extension project in Kiruna-mine, KUJ1365. The quality effects of use of bolting rigs are analysed based on Boltometer and bolt pull testing in KUJ1365 project. Reference material about traditional hand bolting is collected from tunnelling projects run by Lemminkäinen. Based on the collected material, the safety, quality and feasibility of mechanized bolting rigs and traditional hand bolting are compared. Vaikka mekanisoituja pultituslaitteita on ollut markkinoilla ja käytössä kaivoksilla jo suhteellisen pitkään, on niiden käyttö kalliorakennushankkeissa edelleen hyvin vähäistä. Tämän työn tavoitteena oli selvittää mekanisoitujen pultituslaitteiden käyttömahdollisuuksia ja soveltuvuutta kalliorakennushankkeisiin. Työhön on koottu laitevalmistajilta saatujen tietojen pohjalta yleiskuvaus Atlas Copcon ja Sandvikin valmistamien pultituslaitteiden toimintaperiaatteista ja ominaisuuksista. Lisäksi työhön on kerätty käyttökokemuksia Atlas Copcon valmistamista pultituslaitteista Lemminkäisen työkohteissa Kiirunan, Pahtavaaran ja Svartlidenin kaivoksilla. Pultituslaitteiden vaikutusta työturvallisuuteen on arvioitu pultitustyön yleisten riskien ja Lemminkäinen Infra Oy:n, Länsimetro-hankkeen ja Kiirunan kaivoksen KUJ1365-projektin ...